2017
DOI: 10.1371/journal.pone.0169556
|View full text |Cite|
|
Sign up to set email alerts
|

Buzz Factor or Innovation Potential: What Explains Cryptocurrencies’ Returns?

Abstract: Cryptocurrencies have become increasingly popular since the introduction of bitcoin in 2009. In this paper, we identify factors associated with variations in cryptocurrencies’ market values. In the past, researchers argued that the “buzz” surrounding cryptocurrencies in online media explained their price variations. But this observation obfuscates the notion that cryptocurrencies, unlike fiat currencies, are technologies entailing a true innovation potential. By using, for the first time, a unique measure of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 33 publications
1
74
0
Order By: Relevance
“…Wang and Vergne (2017) use the level of newspaper mentions of Bitcoin to proxy for the "buzz" of Bitcoin. They document that high "buzz" predicts low Bitcoin returns in the future Mai et al (2016).…”
mentioning
confidence: 99%
“…Wang and Vergne (2017) use the level of newspaper mentions of Bitcoin to proxy for the "buzz" of Bitcoin. They document that high "buzz" predicts low Bitcoin returns in the future Mai et al (2016).…”
mentioning
confidence: 99%
“…This notion was supported by Bouoiyour and Selmi (2015), who also found BTC to be a speculative bubble rather than being related to market forces. Wang and Vergne (2017) used newspaper mentions of BTC as a proxy for "buzz" and found that high "buzz" was followed by low BTC returns. On the other hand, Van Wijk (2013) focussed on macroeconomic factors, such as stock market indices, oil prices and exchange rates, and found that certain foreign currency pairs, such as Euro/USD and oil prices, share significant relationships with BTC in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although cryptocurrencies were first introduced as a media of exchange for daily payments (Ali et al, 2014), they are increasingly used for speculation (Glaser et al, 2014). Cryptocurrencies can be traded in online exchange platforms and extensive research has looked at the nature and main usages of Bitcoin, specifically in the hope of finding some hints on the price drivers (Kristoufek, 2015;Ciaian et al, 2016;Elendner et al, 2016;Gandal and Halaburda, 2016;Wang and Vergne, 2017;Gajardo et al, 2018;Guo and Antulov-Fantulin, 2018). Comparisons between cryptocurrencies exchange market and the stock market (Ali et al, 2014;Ceruleo, 2014) or fiat currencies (Yermack, 2013) have been drawn, in an attempt to rationalize the market and its price movements.…”
Section: Introductionmentioning
confidence: 99%